Networks, models and decisions: a bibliometric analysis of scientific production on public policy formulation - Gonçalves, Wellington; Romeiro, Pâmella de Medeiros; Gonçalves, William; Mattos, Aliomar Lino; Nepomoceno, Francielle Correa (Brazilian Journal of Production Engineering, 2026)
This work analyzed the evolution of scientific production on public policy formulation between 1977 and 2025, highlighting the relevance of sociopolitical networks, decision-making models, and digital governance as central elements in redefining the relationships between the State, government, and society. The relevance of the research lies in the need to understand how the incorporation of digital technologies and international cooperation influence the State’s capacity to respond to social demands, offering support to both academia and the professional market. The objective was to map historical trends, identify collaboration patterns, and evaluate conceptual transformations, which was carried out through a systematic review and bibliometric analysis of 132,191 publications indexed in the Web of Science (WoS) database. The methodological approach involved the selection of thematic descriptors, the organization of records, and the application of specialized software for visualizing networks and clusters. The results showed continuous growth in academic production, concentration in areas such as Environmental Sciences and Public Health, as well as the formation of international collaborative centers that promote the dissemination of multi-criteria and hybrid decision-making models. Therefore, it was possible to conclude that public policy formulation constitutes an expanding field, marked by interdisciplinarity and the need for more responsive and inclusive policies in the digital age.